Strategic incompatibility in ATM markets - Knittel, Christopher R.; Stango, Victor (Journal of Banking & Finance, 2011)
We test whether firms use incompatibility strategically, using data from ATM markets. High ATM fees degrade the value of competitors’ deposit accounts, and can in principle serve as a mechanism for siphoning depositors away from competitors or for creating deposit account differentiation. Our empirical framework can empirically distinguish surcharging motivated by this strategic concern from surcharging that simply maximizes ATM profit considered as a stand-alone operation. The results are consistent with such behavior by large banks, but not by small banks. For large banks, the effect of incompatibility seems to operate through higher deposit account fees rather than increased deposit account base.